Analisis Daya Saing Ekspor Komoditi Unggulan Perkebunan Indonesia di Pasar Internasional - Hidayati, Berlina; Devi, Hervina Renovaka Pradev; Hermanto, Febrika Yogie; Adinata, Restu Eri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the competitiveness value of Indonesia's exports in plantation commodities during 2018 - 2022. This research is motivated by the increasing growth in the production volume of Indonesian plantation commodities, so it is necessary to examine whether this growth is also accompanied by the value of competitiveness in the international market. This research uses import-export data obtained from the United Nation Commodity Trade and the Revealed Comparative Advantage (RCA) analysis method. The research results show that Indonesian exports of palm oil, rubber, copra and coffee consistently have high competitiveness in the international market. However, clove and pepper commodities will experience a decline or low competitiveness in 2022 with values ​​of 0.2 and 0.9. The competitiveness of Indonesia's exports in plantation commodities remained strong during the pandemic and was able to become a pillar of the economy. This indicates that the government needs to pay attention to the plantation sector in a sustainable manner